1994
DOI: 10.1007/bf02940339
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of adenosine single-photon emission computed tomographic thallium imaging in medically treated patients with angiographic evidence of coronary artery disease

Abstract: Thus adenosine single-photo emission computed tomographic thallium imaging provides important prognostic data in medically treated patients with CAD. The extent of thallium abnormality is the most important predictor of events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Second, MPI has been reported to be limited in its ability in women, as it has been found to produce false-positive results due to breast attenuation and small left ventricular chamber size [40]. Despite this limitation, many studies have reported women with an abnormal MPI finding to be at significantly increased risk for cardiac events [41][42][43][44][45][46][47]. Berman et al [41] found that the greater the abnormality of the MPI is, the greater is the risk of cardiac death in men and women, with diabetic women appearing to be at greater risk of cardiac death than diabetic men for any MPI result.…”
Section: Discussionmentioning
confidence: 99%
“…Second, MPI has been reported to be limited in its ability in women, as it has been found to produce false-positive results due to breast attenuation and small left ventricular chamber size [40]. Despite this limitation, many studies have reported women with an abnormal MPI finding to be at significantly increased risk for cardiac events [41][42][43][44][45][46][47]. Berman et al [41] found that the greater the abnormality of the MPI is, the greater is the risk of cardiac death in men and women, with diabetic women appearing to be at greater risk of cardiac death than diabetic men for any MPI result.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with known CAD, the severity of perfusion defects is associated with increased cardiac risk [14,15]. Normal MPI results, even in patients with multivessel CAD, portend a very favorable prognosis, with a low risk of cardiac events [16,17].…”
Section: Value Of Physiologic Imagingmentioning
confidence: 99%
“…Kamal et al [30] evaluated 177 patients with CAD with adenosine Tl SPECT. Actuarial life-table analysis showed that patients with a perfusion defect size less than 15% had better event-free survival than patients with defects of 15% or greater.…”
Section: Patients With Known or Suspected Coronary Diseasementioning
confidence: 99%